2013
DOI: 10.1136/annrheumdis-2012-202696
|View full text |Cite
|
Sign up to set email alerts
|

MRI comes of age in RA clinical trials

Abstract: The success of modern rheumatoid arthritis (RA) therapies and treatment strategies has led to extended placebo phases being unethical in RA randomised controlled trials (RCTs). Modern trials therefore increasingly involve active comparator designs, and this together with some technical issues has meant difficulties in differentiating structural progression using traditional radiographic outcome measures. Magnetic resonance imaging (MRI) has been demonstrated to assess damage more sensitively than radiographs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Some studies have demonstrated that 30% of patients in remission had radiographic progression, 96% had synovitis and 35% had osteitis 6 7. MRI therefore enables a more sensitive assessment of disease activity, detection of early markers of disease progression and provides a sensitive measure of therapeutic response 8 9…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that 30% of patients in remission had radiographic progression, 96% had synovitis and 35% had osteitis 6 7. MRI therefore enables a more sensitive assessment of disease activity, detection of early markers of disease progression and provides a sensitive measure of therapeutic response 8 9…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal treatment strategy of patients with early RA (ERA), including choices such as initial monotherapy versus combination therapy, and the role of glucocorticosteroids and biological agents has still not been settled 2 3. Trials including active comparators rather than a traditional placebo arm, require sensitive outcome measures to be able to distinguish reliably between therapeutic strategies 4 5…”
Section: Introductionmentioning
confidence: 99%
“…MRI has demonstrated criterion validity for osteitis and synovitis with histology and construct validity for erosions when compared with CT 3 4. Numerous studies have demonstrated MRI to be more sensitive than X-ray in detecting joint damage and to detect synovitis and osteitis more sensitively than clinical examination does.…”
Section: Introductionmentioning
confidence: 99%